2020
DOI: 10.3390/ijms21197332
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk Profiling in Parkinson’s Disease and Utilizing Genetics to Gain Insight into Disease-Related Biological Pathways

Abstract: Parkinson’s disease (PD) is a complex disorder underpinned by both environmental and genetic factors. The latter only began to be understood around two decades ago, but since then great inroads have rapidly been made into deconvoluting the genetic component of PD. In particular, recent large-scale projects such as genome-wide association (GWA) studies have provided insight into the genetic risk factors associated with genetically ‘’complex’’ PD (PD that cannot readily be attributed to single deleterious mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 110 publications
0
17
0
Order By: Relevance
“…Furthermore, substantial cumulative risk was reported by risk profile analysis [51]. GSA generated polygenic risk scores (PRS) for prediction of risk and progression of Parkinson's disease (PD), to search PD-related biological pathways from large-scale pathway specific-genetic risk profiling, and to identify causal PD genes and potential therapeutic targets [52]. Furthermore, increasing evidence suggests that epigenetic mechanisms play a role in regulation of PD-associated genes, including DNA methylation, histone modifications, and microRNAs (miRNSs) [53].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, substantial cumulative risk was reported by risk profile analysis [51]. GSA generated polygenic risk scores (PRS) for prediction of risk and progression of Parkinson's disease (PD), to search PD-related biological pathways from large-scale pathway specific-genetic risk profiling, and to identify causal PD genes and potential therapeutic targets [52]. Furthermore, increasing evidence suggests that epigenetic mechanisms play a role in regulation of PD-associated genes, including DNA methylation, histone modifications, and microRNAs (miRNSs) [53].…”
Section: Discussionmentioning
confidence: 99%
“…Genetics can be used in multiple ways to identify potential genes, proteins, pathways, and networks that may be involved in the pathogenesis of PD and could potentially be therapeutically targeted [ 50 ]. The simplest way of identifying targets using genetics is by examining genes known to cause disease or increase risk, like LRRK2 and GBA , using linkage and sequencing studies in families and sporadic cases.…”
Section: Genetics As a Tool To Nominate Network To Be Targeted Inmentioning
confidence: 99%
“…Genetic factors that cause or increase risk of developing PD include mutations in SNCA (encoding α-synuclein), PRKN , and DJ-1 , among others ( Hall et al, 2020 ). Interestingly, several of these genetic factors have been shown to contribute to immune defense against infectious agents.…”
Section: Introductionmentioning
confidence: 99%
“…Authors showed this to be due to enhanced phagocytosis and bactericidal activity in DJ-1 -deficient macrophages, adoptive transfer of which could rescue septic wildtype mice ( Amatullah et al, 2016 ). Although genetic mutations account for only 5–15% of all PD cases ( Hall et al, 2020 ), better understanding these genetic causes of disease have informed the pathophysiology of the more common sporadic disease cases.…”
Section: Introductionmentioning
confidence: 99%